The Lyapunov–Schmidt Approach to Studying Homoclinic Splitting in Weakly Perturbed Lagrangian and Hamiltonian Systems - Samoilenko, A.M.; Prykarpatsky, A.K.; Samoylenko, V.Hr. (Український математичний журнал, 2003)
We analyze the geometric structure of the Lyapunov–Schmidt approach to studying critical manifolds of weakly perturbed Lagrangian and Hamiltonian systems. Наведено аналіз геомеїричпої структури методу Ляпунова - Шмідта для вивчення критичних многовидів слабкозбурених лагранжевих і гамільтонових систем.